Are two beneficial mutations (p.Q249R and 90-bp Indel) within the ovine BMPRIB gene associated with growth traits? - Xu, Hongwei; Akhmet, Nazar; Luo, Yunyun; Guo, Zhenggang; Pan, Chuanying; Song, Enliang; Malmakov, Nurlan; Akhatayeva, Zhanerke; Lan, Xianyong (Frontiers in Veterinary Science, 2024)
Background: The problem of economic efficiency of sheep breeding can be largely solved by increasing sheep productivity. Recently, the BMPRIB gene has been revealed by GWAS as a candidate gene for sheep body morphometric traits. Therefore, the objective of the present study was to investigate whether genetic polymorphisms (p.Q249R SNP and 90-bp deletion) in the BMPRIB gene are associated with sheep growth traits. Methods: PCR-based genotyping was performed on 1875 sheep, including 1191 Guiqian semi-fine wool (GQSFW), 560 Luxi Blackhead (LXBH), 55 Lanzhou fat-tailed (LZFT), and 69 Weining (WN)sheep. Genotype-phenotype association was assessed using the independent samples t-test and ANOVA. The significance level was set at αoriginal <0.05. The threshold P value for significance was adjusted after correction for multiple comparisons using the Bonferroni correction.2 This is a provisional file, not the final typeset article Results: After Bonferroni correction, it was found that individuals with FecB + /FecB + genotypes of the p.Q249R had significantly better growth traits in LXBH ewe lambs, including body length, chest width, paunch girth, cannon circumference, hip width (P < 0.0005). Meanwhile, associations were observed between 90-bp deletion polymorphism and several growth traits (body length, body height, chest depth and canon circumference) in GQSFW ewe adults after Bonferroni correction (P < 0.0002), and individuals with the "DD" genotypes had greater growth traits.Our findings coincide with experimental observations in the GWAS, in which the BMPRIB gene was proposed as a candidate gene for body measurement traits, while confirm and extend those results. Therefore, further investigations regarding the impact of BMPRIB polymorphisms on growth traits are necessary in other sheep breeds.